The Effect of Capital Structure and Profitability on Firm Value, Moderated by Liquidity, Among F&B Companies Listed on the Indonesian Stock Exchange from 2020 To 2024 - M Farda Najih Arifani; Dian Purnomo Jati; Rini Dwiyani Hadiwidjaja (CV. Publikasi Indonesia, 2026)
This research examines the effect of capital structure and profitability on firm value, with liquidity as a moderating variable, among food and beverage (F&B) manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research is motivated by inconsistent findings in previous studies and the unique financial conditions faced by the F&B sector following the COVID-19 pandemic, including supply chain disruptions, inflationary pressures, and changing consumer behavior. A quantitative approach was employed using secondary data from annual reports, 208 panel observations were analyzed through panel data regression and Moderated Regression Analysis (MRA), with model selection via Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that capital structure has a significant negative effect on firm value, indicating that excessive leverage reduces market valuation. Profitability also demonstrates a significant negative effect on firm value, reflecting investor concerns regarding earnings sustainability during post-pandemic recovery. Liquidity has a significant negative direct effect on firm value, suggesting that excessive current assets may be perceived as inefficient resource utilization. However, liquidity significantly strengthens the relationship between capital structure and firm value, as well as between profitability and firm value, confirming its strategic moderating role in translating financial decisions into market value. This study contributes to corporate finance literature by providing empirical evidence on the moderating role of liquidity in the Indonesian F&B industry during the post-pandemic period and offers practical implications for managers and investors in optimizing financial policies.